2009
DOI: 10.1086/597476
|View full text |Cite|
|
Sign up to set email alerts
|

Plasma Levels of Bacterial DNA Correlate with Immune Activation and the Magnitude of Immune Restoration in Persons with Antiretroviral‐Treated HIV Infection

Abstract: The significance of elevated plasma levels of bacterial lipopolysaccharide (LPS) in persons with chronic HIV infection remains undefined. We measured LPS levels by use of limulus lysate assay, and DNA sequences encoding bacterial ribosomal 16S RNA (16S rDNA) were assessed by quantitative polymerase chain reactions in plasma samples obtained from 242 donors. Plasma levels of 16S rDNA were significantly higher in human immunodeficiency virus (HIV)–infected subjects than in uninfected subjects, and they correlate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

27
520
4
15

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 518 publications
(566 citation statements)
references
References 34 publications
27
520
4
15
Order By: Relevance
“…However, the underlying pathogenic mechanisms are still a topic of debate. Three potential causes of immune activation have been identified, as follows: 1) increased translocation of microbial products across the gut wall (12), 2) CMV coinfection (13,14), and 3) residual low-level HIV replication, identified in studies of ART intensification therapy with HIV integrase inhibitors (15,16). Irrespective of whether one or more of these factors cause persistent immune activation, we and others have demonstrated that elevated expression of IFNstimulated genes (ISG) in separated CD4 + T cells (17), separated accessory cells (18), or PBMC (19) is the strongest correlate of persistent CD4 + T cell deficiency in treated HIV patients.…”
mentioning
confidence: 99%
“…However, the underlying pathogenic mechanisms are still a topic of debate. Three potential causes of immune activation have been identified, as follows: 1) increased translocation of microbial products across the gut wall (12), 2) CMV coinfection (13,14), and 3) residual low-level HIV replication, identified in studies of ART intensification therapy with HIV integrase inhibitors (15,16). Irrespective of whether one or more of these factors cause persistent immune activation, we and others have demonstrated that elevated expression of IFNstimulated genes (ISG) in separated CD4 + T cells (17), separated accessory cells (18), or PBMC (19) is the strongest correlate of persistent CD4 + T cell deficiency in treated HIV patients.…”
mentioning
confidence: 99%
“…So as CD4+ T-cell numbers decrease in HIV condition, HLA-DR+ and CD38+ CD8+ T lymphocytes rather appreciate in numbers [5]. Further studies has also established that viral load cannot separately determine the rate of progression to AIDS, and that immune activation better reflects variations in CD4+ T-cell stronger and independent of viral load [6][7][8][9].…”
Section: Open Access Http://scidocorg/ijmaiphpmentioning
confidence: 99%
“…Bacterial translocation from the GI tract to the peripheral circulation has been extensively studied in HIV infection, but is also common in liver disease and other conditions (24)(25)(26)(27). Translocation occurs early in HIV infection due to depletion of gut CD41 lymphocytes and is not completely eradicated by ART, particularly in patients with a suboptimal CD4 cell count or HIV viral level responses (25,28). Persistent systemic exposure to bacterial antigens from MT triggers immune activation and inflammation in HIVinfected adults (25,26).…”
Section: Bacteria and The Gi Tractmentioning
confidence: 99%
“…Translocation occurs early in HIV infection due to depletion of gut CD41 lymphocytes and is not completely eradicated by ART, particularly in patients with a suboptimal CD4 cell count or HIV viral level responses (25,28). Persistent systemic exposure to bacterial antigens from MT triggers immune activation and inflammation in HIVinfected adults (25,26). MT is associated with T-cell activation, which predicts systemic inflammation, mortality, HIV progression, and progression of comorbidities such as cardiovascular disease (25,26,(29)(30)(31).…”
Section: Bacteria and The Gi Tractmentioning
confidence: 99%
See 1 more Smart Citation